Flavius Patricius, consul for the year 500 - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2022)
This article is devoted to Flavius Patricius, consul for the year 500. For several years he was a close associate of the emperor Anastasius, who entrusted him with important tasks in the military, civil and religious spheres, which indicated that he placed his confidence and esteem in him. During the election of the ruler in July 518, it was probably him who was proclaimed emperor by the guards subordinate to Celer, magister officiorum. This appointment was thwarted by the subordinates of Justin, the comes excubitorum. At the start of the reign of Justin I (late 518, early 519), after intervening in Edessa against the local bishop Paul, Patricius fell out of favour, was deprived of his property and sentenced to exile. After this event he disappears from the sources.